IMPLEMENTASI APLIKASI ACCURATE DALAM PEMBUATAN LAPORAN KEUANGAN PADA PT SRJ - Sopyan, Rizaldy Muhamad; Paryati, Retno (Politeknik Negeri Ambon, 2025)
Introduction: This research focuses on evaluating the adoption of the Accurate application in the financial recording and reporting system at PT SRJ, which had previously relied on a manual approach using physical notebooks and Microsoft Excel. The prior system encountered several limitations, including restricted capabilities, susceptibility to recording mistakes, and insufficient data backup, all of which hindered operational efficiency and the reliability of financial information. Methods: A qualitative research method was applied, utilizing interviews, observations, and document analysis, with a phenomenological perspective. The PIECES framework was employed to assess the system’s performance. Results: Findings reveal that Accurate has a substantial positive impact on the company’s financial operations by facilitating automated transaction entry, delivering real-time financial reports, and enhancing data protection. The PIECES analysis reflects improvements across all dimensions, notably in operational efficiency and internal controls. Therefore, the Accurate application proves to be an effective tool in strengthening the accounting information system within the organization. Keywords: Accurate, Accounting Information System, Financial Report